Synthesis and characterization of organotin (IV) complexes of tridentate schiff bases containing -ono-donor atoms - Foo, Irene Ping Ping. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Six o rganot in(IV) complexes of salicylaldehyde-carbohydrazone ligand (1) with RnSnC4_n (n = 1,2) have been synthesized in the presence of base and refluxing methanol in 1:2:1 molar ratio (metal:base:ligand). Two diorganotin(IV) complexes of salicylaldehyde-L-valine ligand (2) in 1:2: 1 molar ratio (metal:base:ligand) have also been synthesized with same method. All organotin(IV) complexes (3-10) have been characterized using CHN analysis, UV -Visible and IR spectral studies. All organotin(lV) complexes (3-10) are non electrolytic in nature. Spectral studies suggested that both the ligands (1-2) act as a dinegative tridentate nature in their organotin(IV) complexes. Therefore, a five coordinated molecular structure has been proposed for all the mentioned organotin(lV) complexes.